Analisis kemampuan berhitung materi bilangan kelas VII di SMP Negeri 1 Konawe - Dani, Ryan; Hermanto; Kaharuddin, Andi (Karoteh Utama, 2021)
This study aims to analyze students' numeracy skills. This type of research is qualitative descriptive, providing an in-depth depiction of students' numeracy skills as the primary focus, utilizing a qualitative approach based on collected data. The research subjects consist of 6 students from the seventh grade of SMP Negeri 1 Konawe, divided into three categories: high numeracy skills (2 subjects), moderate numeracy skills (2 subjects), and low numeracy skills (2 subjects). Subject selection was based on the previous Daily Test (UH) scores. Data collection techniques employed included tests and interviews. Students' numeracy skills are categorized into three levels: high numeracy skills, moderate numeracy skills, and low numeracy skills. These numeracy skills encompass three main aspects: the ability to solve multiplication operations, the ability to solve division operations, and the ability to connect multiplication and division operations. Subjects 1 (S1) and 2 (S2) in the high numeracy skills category successfully met all three aspects. In contrast, Subjects 3 (S3) and 4 (S4) in the moderate category, as well as Subjects 5 (S5) and 6 (S6) in the low category, have yet to achieve all these aspects.